2021
DOI: 10.3390/app12010277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Germination Black Soy Milk Fermented with Lactobacillus plantarum TWK10 on Anti-Oxidative and Anti-Melanogenesis

Abstract: Black soybean germination or fermentation increases active ingredient bioavailability and anti-oxidative activity. This study investigated the effects of fermented and germinated black soy milk on anti-oxidation and melanogenesis inhibition. The total phenolic content (TPC; 42.66 ± 1.65 mg gallic acid equivalent/g) and total flavonoid content (TFC; 5.43 ± 0.54 mg quercetin equivalent (QE)/g) in ethanol extracts from Lactobacillus plantarum TWK10 (TWK10)-fermented nongermination black soy milk (FNGB) were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Not only extracts may be applied as a potential source of skin-whitening agents, but fermented plant materials can also serve as such. For example, Liu et al have shown that ethanol extracts from Lactobacillus plantarum TWK10 fermented-nongerminated black soy milk and fermented-germinated black soy milk could inhibit melanogenesis, indicating their potential as whitening agents in cosmetic products [150]. The extracts of Aloe vera leaf skin fermented with Lactobacillus plantarum BN41 were tested for their whitening properties.…”
Section: Musa Sapientum Rejected Unripe Fruit Extractsmentioning
confidence: 99%
“…Not only extracts may be applied as a potential source of skin-whitening agents, but fermented plant materials can also serve as such. For example, Liu et al have shown that ethanol extracts from Lactobacillus plantarum TWK10 fermented-nongerminated black soy milk and fermented-germinated black soy milk could inhibit melanogenesis, indicating their potential as whitening agents in cosmetic products [150]. The extracts of Aloe vera leaf skin fermented with Lactobacillus plantarum BN41 were tested for their whitening properties.…”
Section: Musa Sapientum Rejected Unripe Fruit Extractsmentioning
confidence: 99%
“…Studi membuktikan bahwa proses fermentasi dapat meningkatkan mutu gizi serta menurunkan senyawa anti gizi seperti tanin dan saponin (Chaturvendi & Chakraborty 2022). Selain itu, studi terbaru dari Liu et al (2022) menyimpulkan bahwa proses fermentasi pada kedelai hitam terbukti dapat meningkatkan kapasitas antioksidan secara signifikan, serta mampu menghambat proses melanogenesis. Proses fermentasi oleh Rhizopus pada kedelai hitam memicu pembentukan isoflavon yang lebih tinggi dibandingkan pada kedelai hitam tanpa fermentasi.…”
Section: Pendahuluanunclassified
“…Lactobacillus plantarum bacteria grow well in soymilk, produce some bioactive peptides and reduce soy oligosaccharides in a strain-specific manner ( 9 ). Lactobacillus plantarum fermentation improves the antioxidant activity of soymilk food products ( 10 ). The soymilk fermented with L. plantarum was also found to lower the concentration of total cholesterol, triglyceride and low-density lipoprotein cholesterol in serum ( 11 ).…”
Section: Introductionmentioning
confidence: 99%